Low concentrations of acetamiprid, deltamethrin, and sulfoxaflor, three commonly used insecticides, adversely affect ant queen survival and egg laying - Jakub Svoboda; Pavel Pech; Petr Heneberg (Scientific Reports, 2023)
Abstract Ants are key ecosystem service providers and can serve as important biological control agents in pest management. However, the effects of insecticides on common farmland ant species are poorly understood. We tested the effects of three commonly used insecticides on ants (Hymenoptera, Formicidae). The tested insecticides were acetamiprid (neonicotinoid; formulated as Mospilan 20 SP), deltamethrin (pyrethroid; formulated as Sanium Ultra), and sulfoxaflor (sulfilimine; formulated as Gondola). We tested two ant (Hymenoptera: Formicidae) species with different colony founding strategies, Lasius niger (Linnaeus, 1758) and Myrmica rubra (Linnaeus, 1758). We sprayed their queens with insecticides at concentrations recommended for use in foliar applications in agriculture, i.e., at 1.25 g L−1 (acetamiprid), 0.6 g L−1 (sulfoxaflor), and 0.875 g L−1 (deltamethrin). Further, we diluted the compounds in distilled water and tested them at 10%, 1%, and 0.1% of the field-recommended concentrations, and used distilled water as a control. We monitored the survival of the queens and the number of eggs laid. All three tested insecticides caused severe lethal and sublethal concentration-dependent effects. Even at concentrations three orders of magnitudes lower than recommended for field applications, significantly lower numbers of eggs were found in the queens’ nests. The extent of the sublethal effects of acetamiprid and sulfoxaflor was concentration-dependent and differed between the two ant species. Besides bees and bumblebees, ants represent an important group of hymenopterans that are severely affected even by low concentrations of the tested compounds and therefore should be included in risk assessment schemes.